The oddly pedestrian life of Christopher Chaos - Brombal, Tate; Tynion, James IV 1987- (Dark Horse Books, a division of Dark Horse Comics, 2024)
"Collects The oddly pedestrian life of Christopher Chaos #1-6 and a ten-page prolouge"--Tp verso